Advanced Methods for Seismic Performance Evaluation of Building Structures - Han, Sang Whan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue was created to collect the most recent and novel research on seismic performance evaluation of building structures. This issue includes three important topics on seismic engineering for building structures: (1) seismic design and performance evaluation, (2) structural dynamics, and (3) seismic hazard and risk analysis. To protect building structures from earthquakes, it is necessary to conduct seismic performance evaluations on structures with reliable methods and to retrofit these structures appropriately using the results of the seismic performance evaluation.